2023
DOI: 10.1039/d3bm01095c
|View full text |Cite
|
Sign up to set email alerts
|

Applications of microalga-powered microrobots in targeted drug delivery

Min Zhou,
Yannan Yin,
Jiuhong Zhao
et al.

Abstract: Over the past decade, microalgae are considered potential drug delivery carriers. Microalgae-based drug delivery systems have excellent biocompatibility and unique motor characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 117 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…Different types of single-cell microrobots, such as cell-based microrobots, bacteriabased microrobots and algae-based microrobots [27], have been largely developed in recent years [98] to exploit the natural mobility and other features of cells/organisms for the transport and biodistribution of different drugs [99]. Cell-based microrobots, such as erythrocytes, sperm cells [100], leukocytes and other motile cells driven microrobots, are considered effective for targeted drug delivery, due to their escape mechanisms and biocompatibility [98].…”
Section: Nano-"magic Bullets" In Bc Theranosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of single-cell microrobots, such as cell-based microrobots, bacteriabased microrobots and algae-based microrobots [27], have been largely developed in recent years [98] to exploit the natural mobility and other features of cells/organisms for the transport and biodistribution of different drugs [99]. Cell-based microrobots, such as erythrocytes, sperm cells [100], leukocytes and other motile cells driven microrobots, are considered effective for targeted drug delivery, due to their escape mechanisms and biocompatibility [98].…”
Section: Nano-"magic Bullets" In Bc Theranosticsmentioning
confidence: 99%
“…Magnetic bacteria-based bio-hybrid microrobots are a widely used living material in the field of magnetically driven diagnostics [101] as well as for targeted cancer therapy [102]. Microalgae, due to their high biocompatibility, low costs, large active surface area, strong anti-cancer drug and NPs absorption capability, phototaxis, oxygen production and high-speed of propulsion, can be successfully used as oxygenators, micro-or nanoswimmers and ideal carriers for efficient drug loading and precise targeted DDS [99,103]. Thus, Zhong et al (2020) reported the efficacy of a biodegradable microalgaebased carrier, Spirulina platensis, for the targeted delivery of doxorubicin and non-invasive fluorescence imaging-guided therapy on lung metastasis of 4T1 mouse BC cells [27].…”
Section: Nano-"magic Bullets" In Bc Theranosticsmentioning
confidence: 99%